Effects of Brimonidine on Microglia Morphology in the Transient Retinal Ischemia Model - Ekicier Acar, Selcan; Sinan Sarıcao ˘glu, M; Çolak, Aysel; Akta¸s, Zeynep; Sepici Dincel, Aylin (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
Background: This study aimed to investigate the effects of brimonidine on microglia cell morphology by creating a transient retinal ischemia model in rats. Methods: In the right eyes of male Wistar rats (n = 12), a transient retinal ischemia model was created. The rats were divided into three groups: (1) eyes treated with topical brimonidine in the transient retinal ischemia model, (2) shamtreated eyes, and (3) control eyes. Four main phenotypes (ramified, primed, reactive, and amoeboid-phagocytic) of Iba-1 positive microglia cells were examined in the retinal layers. Results: In the transient retinal ischemia model, the number of Iba-1 positive microglia cells was 100.67 ± 7.50 cells in the sham group and 57.67 ± 14.64 cells in the topical brimonidine group. The decrease in the total number of Iba-1 positive microglial cells was statistically significant (p < 0.05). When we compared ramified and primed microglia cells, there was no statistically significant difference between the groups. The number of amoeboidphagocytic microglial cells was 9.5 ± 1.29 cells in the sham treatment group and 2.25 ± 0.50 cells in the topical brimonidine group (p < 0.05). There was a statistically significant decrease in the number of reactive and amoeboid cells. Conclusion: Studies in the central nervous system in rats demonstrated that cell metabolism and functions were changed after acute injury and that microglia transformed from a ramified form to an amoeboid-phagocytic form. In this study, the decrease in the transition of cells from ramified to reactive and amoeboid forms showed us that topical brimonidine treatment could have neuroinflammation suppressor features.